Protective Activity of Aqueous Extracts from Higher Mushrooms Against Herpes sipmlex Virus Type-2 on Albino Mice Model - I. A. Razumov; E. I. Kazachinskaya; L. I. Puchkova; T. A. Kosogova; I. A. Gorbunova; V. B. Loktev; T. V. Teplyakova (Антибиотики и Химиотерапия, 2020)
Toxicity and antiviral activity of aqueous extracts from higher mushrooms such as Lentinula edodes (Berk.) Pegler (shiitake), Pleurotus ostreatus (Jacq.) P. Kumm. (oyster), Inonotus obliquus (Ach. ex Pers.) Pilat (chaga), Hydnellum compactum (Pers.) P. Karst. (compact tooth) were studied. In doses of 0.8 to 4.0 mg (dry weight) per mouse administered orally or intraperitoneally the extracts showed no acute toxicity. When the dose of the chaga extract was increased to 20 mg per mouse, a half of the animals died. Intraperitoneal administration of the aqueous extracts in a dose of 0.4-2 mg per mouse prior to the contamination by a single LD50 of Herpes simplex type 2 provided 100-percent survival of the animals exposed to the Lentinula edodes or Pleurotus ostreatus extracts and 90-percent survival of the animals exposed to the Inonotus obliquus or Hydnellum compactum extracts.